COUNSELING MULTIKULTURAL - Nuzliah Nuzliah (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2016)
Multicutural is a term used to describe one's view of the variety of life in the world, or cultural policy emphasizing their acceptance of diversity, and a wide range of cultures (multicultural) that exist in society regarding values, system, culture, customs and politics that they profess. The effectiveness of counseling depends on many factors the most important is the relation to each other, and mutual understanding between counselor and client. Cultural differences that exist in this country requires the counselor needs to understand the different cultures that exist. Importance of multicultural for counselors as a form of consciousness that the counselor and client have cultural differences. Multicultural counseling a counseling relationship with the concept that there is a counselor with a client who has a cultural background, values and different lifestyles. Building a good relationship when the counseling process takes place so that the counselor can understand the culture of its clients one of the key attitudes that exist within konsleor is empathy. Counselors who have empathy will be able to understand the way the world through the perspective of the client.